2018
DOI: 10.1097/gox.0000000000001792
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Osteonecrosis after Medial Femoral Condyle Bone Graft Harvest

Abstract: Summary:The medial femoral condyle vascularized graft has become a useful resource in reconstructive microsurgery due to the rate of bony union, and the low rate of complication. We report osteonecrosis of the medial femoral condyle in a 65-year-old woman after harvesting a corticocancellous medial femoral condyle graft to treat a tarsometatarsal nonunion. We were not able to define whether a vascular or mechanical disorder could be the ultimate cause. However, because of the severity of the complication, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Moreover, during our review we did not find more information in connection with MFC graft depth. As an isolated report, Boretto et al 27 informed about the risk of femoral osteonecrosis after the harvest of a MFC flap, suggesting the surgeon to mention this potential complication during patient preoperative counseling. Furthermore, it appears that the current indications allow for an up to 5-cm harvest of MFC without concerns of femoral fracture, 28 even though in a previous work, the same author 26 suggested a larger area of bone available for harvest.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, during our review we did not find more information in connection with MFC graft depth. As an isolated report, Boretto et al 27 informed about the risk of femoral osteonecrosis after the harvest of a MFC flap, suggesting the surgeon to mention this potential complication during patient preoperative counseling. Furthermore, it appears that the current indications allow for an up to 5-cm harvest of MFC without concerns of femoral fracture, 28 even though in a previous work, the same author 26 suggested a larger area of bone available for harvest.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, femoral osteonecrosis after medial condyle bone graft harvest has been reported. 22 The main limitation of the 1,2 ICSRA flap is the treatment of associated scaphoid collapse with humpback deformity. As the scaphoid collapses volarly, a pure dorsal approach to the scaphoid will not allow visualization of the palmar defect and may prevent anatomical correction of the defect, potentially leading to lower union rates.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical studies have demonstrated that a large MFC flap can be harvested without risking the femur fracture at the donor site in axial load application. 11,12,19 An MFC flap may include entire medial surface of the condylar and supracondylar region; however, there are some variations in the literature regarding the supposed dimensional limitations of the MFC flap: 10-13 cm (length), 7-8 cm (width) and 1.5 cm (depth). 2,18 Moreover, the flap is anteriorly limited by the medial patellar facet, posteriorly by the posterior border of femur, and distally by the origin of the medial collateral ligament.…”
Section: Dovepressmentioning
confidence: 99%
“…All of these have contributed to the increasing use of the MFC free flap in reconstructing defects of diverse sizes and designs. [7][8][9][10][11][12][13][14][15]…”
Section: Introductionmentioning
confidence: 99%